2008
DOI: 10.1097/brs.0b013e31816b45c3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Mesenchymal Stem Cells Derived From Adipose Tissue and Bone Marrow for Ex Vivo Gene Therapy in Rat Spinal Fusion Model

Abstract: HATDMSCs transfected with adeno-BMP-2 induce abundant bone formation and have a similar posterolateral spinal fusion in rats as similarly genetically modified HBMDMSCs. Both are potential strategies for spinal fusion and may be a more efficient method of obtaining spinal fusion over currently used grafting substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 28 publications
1
70
0
1
Order By: Relevance
“…Moreover, previously published rat spinal fusion studies assessing autologous bone grafting were observed to yield an inferior fusion rate when compared with hPSC treatment (0% fusion after 4 weeks and 11% fusion after 8 weeks with autologous bone grafting, compared with 80%-100% fusion in 4 weeks with hPSC treatment) [46,47]. MSCs derived from multiple sources such as bone marrow and adipose tissue have attracted large interest for replacement of autogenous bone in spinal fusion procedures [48][49][50][51][52]. BMSCs, however, are limited in supply, and it is estimated that only 1 BMSC can be isolated per 100,000 cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previously published rat spinal fusion studies assessing autologous bone grafting were observed to yield an inferior fusion rate when compared with hPSC treatment (0% fusion after 4 weeks and 11% fusion after 8 weeks with autologous bone grafting, compared with 80%-100% fusion in 4 weeks with hPSC treatment) [46,47]. MSCs derived from multiple sources such as bone marrow and adipose tissue have attracted large interest for replacement of autogenous bone in spinal fusion procedures [48][49][50][51][52]. BMSCs, however, are limited in supply, and it is estimated that only 1 BMSC can be isolated per 100,000 cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Radiographic analysis (Fig. 3) revealed that the new bone mass between the L4 and L5 transverse processes in the Nell-1 (5.0 mg) group was the most radiopaque, and a continuous bony bridge formed between the transverse processes.…”
Section: Radiography and Manual Palpationmentioning
confidence: 99%
“…Bone formation in these groups was compared to our previously established positive control of absorbable collagen sponges impregnated with 10 mg recombinant human BMP-2. [32][33][34][35] After anesthesia induction by isoflurane inhalation, the surgical site was shaved and prepped. A posterior midline incision was made over the skin of the lumbar spine.…”
Section: Surgical Procedures and Study Groupsmentioning
confidence: 99%
“…ADSCs expressing bone morphogenic proteins have proven effective for spinal fusion in animal models of metabolic bone disease [32,33] . In a study comparing MSCs and ADSCs expressing BMP-2 seeded on collagen sponges, fusion rates were encouraging and not significantly different in the two groups of rat models [34] . Due to the relatively easier clinical access to ADSCs in the patient, greater attention to their potential role in spinal fusion is warranted.…”
Section: Spine Fusionmentioning
confidence: 99%